2018
DOI: 10.3126/nccj.v3i1.20255
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Stock Market Performance

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The impact of certain macroeconomic parameters such as remittances, money supply, exchange, rate, and interest, rate on securities market performance is investigated in this article. The analysis shows that remittances and money supply have a beneficial impact on the stock market, whereas interest, rates and exchange, rates negatively impact (Rakhal, 2015). According to this study, real M2 does not affect the securities market index (Hsing, 2011).…”
Section: Review Of Literaturementioning
confidence: 51%
“…The impact of certain macroeconomic parameters such as remittances, money supply, exchange, rate, and interest, rate on securities market performance is investigated in this article. The analysis shows that remittances and money supply have a beneficial impact on the stock market, whereas interest, rates and exchange, rates negatively impact (Rakhal, 2015). According to this study, real M2 does not affect the securities market index (Hsing, 2011).…”
Section: Review Of Literaturementioning
confidence: 51%
“…The positive effect of money supply and negative influence of interest rate on NEPSE index were verified by the findings of Shrestha and Pokhrel (2019) and Devkota and Dhungana (2019). Rakhal (2018) found the significant positive effect of remittance and money supply and negative effect of interest rate and exchange rate on the performance of Nepalese stock market. Panta (2020) applied ARDL model and found a strong association of GDP, money supply, inflation, interest rate and exchange rate with performance of Nepalese stock market in long-run.…”
Section: Introductionmentioning
confidence: 92%
“…The study concluded that the findings are of great interest to readers in the areas of economic forecasting on the base of long memory models. Rakhal (2018) explored the effect of selected macroeconomic factors such as remittances, money supply, exchange rate, and interest rate on stock market performance. The study demonstrates that remittance and money supply positively affect the stock market whereas interest rate and exchange rate negatively affect the stock market performance.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%